التوظيف النفسي لمستأصلات الرحم - بن زيدان, كنزة; مخلوف, سعاد (جامعة الوادي - University of Eloued, 2020)
ملخص: تناولنا في هذا البحث موضوع "التوظيف النفسي لمستأصلات الرحم"، بهدف معرفة نوع التوظيف النفسي لدى المرأة مستأصلة الرحم، تحديد نوع البنية لدى المرأة مستأصلة الرحم، التقرب من المريضة ومعايشتها، ولدراسته اخترنا حالتين قد تم إجراء عملية استئصال الرحم لهما بسبب السرطان، وكان ذلك ذلك في المستشفى الجامعي بالبليدة على مستوى مصلحة مكافحة السرطان بجناح الجراحة، واستندنا في دراسة هذا الموضوع على المنهج العيادي، وعلى هذا الأساس استخدمنا الأدوات التالية: الملاحظة العيادية، المقابلة العيادية والاختبار الإسقاطي "رورشاخ"، وبعد تحليل معطيات هذا الموضوع بناءا على الاتجاه السيكودينامي. وقد توصلنا إلى ما يلي: اشتراك الحالتين في انعدام القدرة التعبيرية والانفعالية، الحرمان العاطفي، وجود مشاكل جنسية تمثلت في انخفاض القوى الليبيدية، قلق على الصحة، التمركز حول الذات، والنرجسية. أما الاختلاف بينهما فيكمن في أن الحالة الثانية تبد بعض العدوانية على عكس الحالة الأولى التي تقوم بكبتها مما يفسر شخصيتها التبعية، انطلاقا من هذه النتائج يمكن تصنيف الحالة في إطار بنية عصابية يميزها الاكتئاب الأساسي . summary : In this research, we dealt with the subject of "psychological employment of hysterectomy", in order to know the type of psychological employment in women hysterectomy, determine the type of structure in the woman hysterectomy, approaching the patient and living, and to study we have selected two cases have been hysterectomy because of cancer, and that was At the university hospital in Blida at the level of the cancer control department in the surgical ward, we were based on the study of this subject on the clinical approach, and on this basis we used the following tools: Clinical observation, clinical interview and projective test "Rorschach", and after analyzing the data of this topic A on the psychodynamic direction. We found the following: the two cases involved in the lack of expressive and emotional ability, emotional deprivation, the existence of sexual problems represented in the decline of Libyan forces, concern for health, self-centered, and narcissism. The difference between them is that the second case shows some aggressiveness, unlike the first case that represses it, which explains its dependency personality, based on these results can be classified into a neurological structure characterized by the underlying depression.
مقال
Keywords: التوظيف النفسي، مستأصلات الرحم; 150 words) ; An abstract is a brief, comprehe